Creating Shared Value: Alternative Business Model Innovation for Financial Products and Services Sector - Chaniago, Fajar Ismi; Koesrindartoto, Deddy Priatmodjo (Syntax Corporation, 2025)
This final project focuses on the phenomenon of business lending as a provider and SMEs as customers/ beneficaries. Businesses are too profit-oriented and often overlook shared value in contributing to the profitability of business activities. The final project objectives are to answer the question of how to implement and measure the Creating Shared Value (CSV) programs and to propose a business model canvas to solve the phenomenon of business lending and SMEs for growing together and also give positive impact. With a qualitative approach, the researcher incorporates information from literature analysis on related topics, in-depth interviews with four interviewees, and reports from related companies. Data analysis guided by the triangulation process as a logic of inquiry has been conceptualised by the researcher within this final project, which differs in its goals, purposes, and literature review through the case study research process. Some providers have not yet implemented CSV, and some providers have implemented CSV but not with measurements that relate to business objectives. Besides that, the proposed business model canvas will help providers to implement the CSV concept.